TELAAH KONSEPTUAL DAN ISU METODE RISET SERTA PENGEMBANGAN MODEL INTEGRASI KEADILAN ORGANISASIONAL (Fokus Ekonomi, 2010)
This article discussed about organizational justice, which is consist of three main dimension; distributive justice, procedural justice, and interactional justice.  Based on empirical review, this article propose integrative model of organizational justice. Each dimension was determined by several factor such as organizational structure, subordinate charisma and team organizational justice. Beside that, organizational justice also determine several attitude and behavior such as satisfaction, commitment, organizational and supervisor trust. This article also discussed about conceptual and research issues in organizational justice.